Perencanaan dan Pengadaan Obat di Puskesmas “X” Berdasarkan Permenkes Nomor 74 Tahun 2016 - Fathiyah Rahmah (Universitas Airlangga, 2018)
Imperfect and inaccurate drugs and medical consumables planning and procurement likely affect their sustainability in Public Health Center (Puskesmas). This paper aims to study the mechanism of drugs planning and procurement implemented by Puskesmas